2019
DOI: 10.18326/rgt.v12i2.157-180
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Scientific-Based Approach in ELT Class to Improve Students’ Achievement and Classroom Interaction

Abstract: This study investigated the use of the scientific-based approach in the ELT class to solve students' learning problems. Those problems are students' difficulties to complete their learning tasks, lack of vocabularies to complete reading tasks, lack of grammatical competence, afraid of proposing questions, afraid of speaking, and difficulties to complete the listening tasks. These caused students to have low achievement and inactive classroom interaction. The study was aimed at improving students' achievement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
(10 reference statements)
1
14
0
Order By: Relevance
“…These findings may help language teachers and learners. English foreign language teachers in Indonesia can develop new ways for English teaching, for instance, by demonstrating to the students the differences between Indonesian and English regarding their grammatical constructions (Haerazi, Vikasari, & Prayati, 2019). Also, teachers can improve students" grammatical knowledge.…”
Section: Taskmentioning
confidence: 99%
“…These findings may help language teachers and learners. English foreign language teachers in Indonesia can develop new ways for English teaching, for instance, by demonstrating to the students the differences between Indonesian and English regarding their grammatical constructions (Haerazi, Vikasari, & Prayati, 2019). Also, teachers can improve students" grammatical knowledge.…”
Section: Taskmentioning
confidence: 99%
“…This activity is intended for students to distinguish or bring together the ideas contained in the reading. These findings were reinforced by Haerazi, Vikasari, and Prayati (2019) who found that small groups are very effective to involve students in discussing learning topics to practice communication and to interact among students-students and students-teachers. The next phase is to Talk.…”
Section: Discussionmentioning
confidence: 98%
“…In the Indonesian context of EFL material development, English teaching is directed to improve students' critical thinking, communication, collaboration, and creativity. It is in accordance with 21 st -century learning skills (Haerazi, Vikasari, & Prayati, 2019). In the research, the analysis is directed to teachers' efforts of incorporating culturebased materials to enhance students' critical thinking skills, achievement, and classroom interaction.…”
Section: Introductionmentioning
confidence: 94%